Research of adhesives used in the stand tests of aircraft structures - Rośkowicz, Marek; Tkaczuk, Sławomir; Leszczyński, Piotr (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2017)
The paper presents the results of their own research, whose aim was comparative analysis of the capacity of the handlesused as nodesthe loading system of aircraft airframes in the stand tests.Handles made of fabric are adhered to the airframe skin in a time consuming and laborious process.It proposed to replace the currently used solvent adhesive Butapren other type of adhesive and at the same time to simplify and shorten the process of attaching handles.A seemingly trivial task, however, turned out a complex problem, because an adhesive jointsare exposed to the least desirable case of load, ie. detaching and the commercially available adhesive application has a much longer cure time than the time declared by the manufacturers. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)